CRUSTAL STRUCTURE OF THE NORTHERN BALTIC SEA PALAEORIFT - Korja A.; Heikkinen P.; Aaro S. (My University, 2001)
Integrated analysis of the gravity data measured in the northern Baltic Sea in 1997 and the near-vertical BABEL data shot in 1989 provides important constraints for the Subjotnian (1600–1500) rift-related evolution of the Svecofennian orogenic crust.The Subjotnian is characterised by voluminous bimodal rapakivi granite magmatism that is manifested as large granite batholiths associated with ovoid crustal thickness minima and large Bouguer gravity minima (−20 to −40 mgal). In the seismic sections, the batholiths are transparent whereas the lower crust beneath is highly reflective and bears signs of intra- and underplating.The Bouguer anomaly map together with the seismic results imply that the crust of the Southern Gulf of Bothnia is mostly composed of Subjotnian intrusions with a large rheologically stronger, mafic Svecofennian block in the middle. The largest batholiths Åland, Bothnian and Rödön are mostly covered by water, but even the minor plutons at Strömsbro, Reposaari and Siipyy are interpreted to be small satellites to larger marine batholiths. A 3–4 km deep Jotnian sandstone basin, the Strömmingsbodan basin, was developed on top of the Bothnian rapakivi granite. We suggest that it was initiated by cauldron subsidence. In the Postjotnian, the granites and sandstones were intruded by diabase sills, the contacts of which are imaged by high-amplitude reflections. The rapakivi granites are separated by a large transparent and dense body in the lower to middle crust. It is interpreted as an older Svecofennian mafic intrusion.The northern Baltic Sea has many characteristic features of paleorifts: topographic low (now under water), thin crust with large crustal thickness gradients and the products of voluminous bimodal magmatism. The Gulf of Bothnia aborted rift is a part of a honeycomb-like wide rift area that extends from Lake Ladoga to the Caledonides It has seeds of many localised narrow rifts not connected at the lower crustal level.